Visualising Tamerlane: History and its Image. Issue 1 (2nd January 2019) - Melville, Charles
ABSTRACT: The creation of Timur's kingly image was the work of his chroniclers and in particular the achievement of 'Ali Yazdi, whose literary masterpiece, the Zafarnama ("Book of Victory"), was commissioned by Timur's grandson, Ibrahim-Sultan, prince governor of Shiraz in southern Persia (r. 1415–1435). Yazdi's work became a byword for rhetorical elegance and was reproduced in many tens of manuscripts; some of these, including the first known copy, dated 1436, were illustrated. Within the corpus of illustrated manuscripts and the paintings they contain, I differentiate between royal or court commissions, such as those produced for Timur's descendants, and provincial or commercial ones produced in the next century, and the effect this may have had on the choice of scenes to illustrate. Among these, it is helpful to distinguish between "generic" scenes of battle, single combats, hunting and the ruler's court, and specific scenes of particular events, often found in a unique image, and their relationship with the written text. While these illustrations cannot be viewed as visual sources for the history of the events they depict, they can be regarded as evidence of how Timur's career was perceived and understood by subsequent generations.